Giant Cell Tumor of Tendon Sheath and Tendinopathy as Early Features of Early Onset Sarcoidosis - Zheng, Shaoling; Lee, Pui Y.; Huang, Yukai; Wang, Aiwu; Li, Tianwang (Frontiers in Pediatrics, 2019)
Giant cell tumor of tendon sheath (GCTTS) is characterized by diffuse proliferation of synovial-like cells and multinucleated giant cells along tendon sheaths. This benign tumor typically presents in the third to fourth decade of life and is exceeding rare in children. Here we describe a case of a 10-years-old girl with a history of soft tissue swelling involving the third digit of left hand, bilateral wrists and ankles. Pathology of the finger mass revealed abundant multinucleated giant cells consistent with GCTTS. Resection of the tendinous masses from the ankles also showed multinucleated giant cells along with chronic bursitis. She began to show features of polyarticular arthritis by age 7. Due to progression of arthritis, whole exome sequencing was performed and found a de novo heterozygous mutation in NOD2 (p. R334Q). This variant is the most common mutation responsible for early onset sarcoidosis (EOS)/Blau syndrome, an autoinflammatory disease characterized by granulomatous inflammation of joints, skin and eyes. The early onset of symptoms and presence of multinucleated giant cells and granuloma in this case are in keeping with a diagnosis of EOS/Blau syndrome. The patient responded well to treatment with methotrexate and etanercept. This case extends the clinical spectrum of EOS/Blau syndrome, which should be considered for GCTTS and other unusual presentations of tendon inflammation in children, even in the absence of the characteristic triad of arthritis, dermatitis and uveitis.